Bridging the digital divide: Innovative approaches to 21-century skill development in work-integrated learning programmes. - Sekano, K. G.; Ramorola, M. Z. (South African Journal of Higher Education, 2026)
Studies have confirmed technology as an enabler of work-integrated learning for 21-century skills. Higher education institutions that offer teacher education in South Africa, however, still struggle with ways to address students' needs and to prepare them for the workplace. Several areas have been identified as posing particular challenges, such as using technology to strengthen co-operative learning, communication, and problem-solving skills required by students for the workplace. In this article, we argue that technology should be incorporated into work-integrated learning to facilitate learning and improve student engagement and self-directed learning. Employing a qualitative research approach, the study on which this article is based used data extrapolated from an open-ended questionnaire completed by participating students (n = 100). The findings revealed that technology provides a platform for students to collaborate, communicate, and solve problems in their diverse groups. The study also found that technology provides opportunities for students to develop creative and critical thinking skills, as well as the possibility to engage actively in group activities. It is recommended that technology be incorporated into work-integrated learning programmes to facilitate learning of the 21st-century skills, improve student engagement, and enhance self-directed learning. By using technology, students can engage in meaningful learning activities that simulate real-world scenarios, promoting active participation and diverse group interactions, which are essential for their future workplace environments.